Birth weight, physical growth and body composition in children: A longitudinal study - Moura dos SANTOS, Marcos André; de França VERÇOSA, Marcela; Queiroz Ferreira GOMES, Thayse Natacha; Ribeiro MAIA, José António; Gois LEANDRO, Carol (Revista de Nutrição, 2023)
Objective To describe children’s physical growth (body mass and height) velocity and body composition (fat percentage and Fat Free Mass); to investigate the magnitude of interindividual differences according to age, gender and birth weight categories, as well as to examine the differences in the average trajectories of children with Low Birth Weight and Normal Weight according to international references. Methods The sample consisted of 534 children (279 boys and 255 girls, 7 to 10 years old) evaluated in the fi rst year of study and followed for 3 years with overlap between the ages of 7 and 9 years. Physical growth and bodycomposition measurements included: height, body mass, fat percentage (%Fat) and Fat Free Mass. Multilevel Modelling was used. Results Birth weight was not associated with physical growth and body composition markers at 7 years old or with the velocity of their changes (p>0.05). There were significant interindividual differences in the trajectories of physical growth (height and body mass; p<0.001) and body composition (%Fat and Fat Free Mass; p<0.001). In plotting on international percentile charts, the trajectories of growth and body composition were within expected values for age and gender, regardless of birth weight. Conclusion There are significant differences in the dynamics of stature growth, body mass and Fat Free Mass, and Low Birth Weight has no influence on this trajectory. In addition, values are within the expected range for age and sex.